2019
DOI: 10.35207/later.537817
|View full text |Cite
|
Sign up to set email alerts
|

Okul Öncesi Eğitim Kurumlarına Devam Eden Mülteci Öğrencilerin Sınıf Ortamında Karşılaştıkları Sorunlara İlişkin Öğretmen Görüşleri

Abstract: Bu araştırmanın amacı, sınıflarında mülteci öğrencisi bulunan okul öncesi eğitim öğretmenlerinin, bu öğrencilerin eğitim-öğretim sürecinde karşılaştıkları sorunlar hakkındaki görüşlerini almak ve karşılaştıkları sorunlar karşısında ne gibi çözümler ürettiklerini ortaya koymaktır. Nitel araştırma yöntemlerinden durum çalışması olarak desenlenen bu çalışmada, amaçlı örnekleme yöntemlerinden ölçüt örnekleme yöntemi ve kolay ulaşılabilir örnekleme yöntemi kullanılmıştır. Örnekleme yönteminde belirlenen ölçüt ise, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 17 publications
(8 reference statements)
0
3
0
4
Order By: Relevance
“…In two different studies with the pre-school students, similar results were found. It was concluded that the level of the Syrian children to know Turkish played an important role in adapting to school, learning class rules, communicating easily with others and feeling secure (Yanık-Özger and Akansel, 2019;Avcı, 2019). It has been emphasized that in all similar studies, the most fundamental issue is language problem (Çerçi and Canalıcı, 2019;Küçüksüleymanoğlu, 2018;ġahin and ġener, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In two different studies with the pre-school students, similar results were found. It was concluded that the level of the Syrian children to know Turkish played an important role in adapting to school, learning class rules, communicating easily with others and feeling secure (Yanık-Özger and Akansel, 2019;Avcı, 2019). It has been emphasized that in all similar studies, the most fundamental issue is language problem (Çerçi and Canalıcı, 2019;Küçüksüleymanoğlu, 2018;ġahin and ġener, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The fact that parents and teachers have different cultural backgrounds in terms of language, religion, national value and country can also cause them to be reluctant to efficiently communicate (Sohn & Wang, 2006). In addition, language problems experienced by children cause them to be unable to communicate with their peers and not participate in classroom activities, which leads to behavior and adaptation problems (Avcı, 2019). The negative attitude and behavior exhibited by refugee families also affects children's adaptation processes to school.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the practices of teachers regarding the adaptation of refugee children to school are important. Previous studies on refugee preschool children have focused on adaptation to school and psychological state (Bozkurt Polat, Özbey, Türkmen, & Köyceğiz Gözeler, 2020;Karaman & Bulut, 2018;Karoly & Gonzalez, 2011;Kiremit, Akpınar, & Tüfekçi, 2018;Kirova, 2010;Lunneblad, 2017;Marsh, 2017;Neitzel et al, 2019;Thommessen & Todd, 2018;Yalçın & Simsar, 2020), peer culture (Yanık Özger & Akansel, 2019), difficulties faced in the process (Avcı, 2019;Aydın & Kurtulmuş, 2018;Mercan Uzun & Bütün, 2016) and family dimension (Dağlar et al, 2011;Sohn & Wang, 2006). However, there is no holistic study in the literature which focuses on the practices of preschool teachers for the adaptation process of refugee children to school, the problems faced by teachers and their strategies to solve these problems, and their recommendations for a better adaptation process of refugee children.…”
Section: Introductionmentioning
confidence: 99%
“…Çokkültürlü ve çok dilli bir eğitim ortamında görev yapan öğretmenlerin hem planlama hem de uygulama süreçlerinde yansıtıcı ve kapsayıcı olabilmek için daha çok çaba göstermesi gerekecektir. Yapılan bazı çalışmalar, sığınmacı çocukların farklı bir dili konuşmaktan kaynaklı çok ciddi sorunlarla baş etmek zorunda kalabildiklerini göstermiştir (Aksakal, 2017;Avcı, 2019;Aykut, 2019;Esen, 2020). Sığınılan ülkenin dilini iyi konuşamayan ve o dilde iletişim kurmakta zorluk çeken çocuklar, yerli akranları tarafından daha yüksek oranda dışlanma riski ile karşı karşıya kalırlar (Gencer, 2017).…”
Section: Introductionunclassified
“…Sığınılan ülkenin dilini iyi konuşamayan ve o dilde iletişim kurmakta zorluk çeken çocuklar, yerli akranları tarafından daha yüksek oranda dışlanma riski ile karşı karşıya kalırlar (Gencer, 2017). Çokkültürlü çocuklarla çalışan öğretmenlerin eğitsel ve iletişimsel açıdan zorlandıkları bilinmektedir (Avcı, 2019;De Beer, 2019;Eroğlu ve Gülcan, 2016). Sığınmacı ailelerin eğitime yeterince katılım göstermekte engellerle karşılaşması, öğretmenin süreç içindeki çabasının yetersiz kalmasına neden olmakta ve öğretmenlerde yetersizlik duygusu oluşturabilmektedir (Aykırı, 2017;Gencer, 2017;Kardeş ve Akman, 2018;Karuppiah, 2004;Şimşir ve Dilmaç, 2018;Vinagre, 2019;Youn, 2016).…”
Section: Introductionunclassified